Effective isolation of Sertoli cells from New Zealand rabbit testis - Zhu, Wen Qian; Yang, De Cai; Jiang, Yu; Cai, Ning Ning; Yang, Rui; Zhang, Xue Ming (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: Sertoli cells (SCs) are important sustentacular cells in the seminiferous tubules of the testis. Isolation and identification of SCs are the premise for studying their functions. Since New Zealand rabbit is a stable strain which is widely used for biomedical research and animal farming, this study aimed to develop a simple and effective protocol for SC isolation in New Zealand rabbits. Materials and Methods: The SCs of three 30-day-old New Zealand rabbits were isolated by incubation with enzymatic digestion I (Dulbecco’s modified Eagle medium supplemented with 1 mg/ ml collagenase IV and 50 μg/ml DNase I) and digestion II (digestion I + 1 mg/ml hyaluronidase + 1 mg/ml trypsin), as well as differential plating. The cells were enriched and identified by using immunocytochemical staining and reverse transcription polymerase chain reaction analysis. Results: Homogeneous cells were obtained. They presented the typical large cell body and an irregular pyramidal shape after differential plating and passaging. These cells expressed mRNA of the SC marker sex-determining region Y-box 9 (SOX9) instead of the Leydig cell marker StAR. Immunocytochemically, they are positive of SOX9, GATA binding protein 4, and androgen-binding protein. Conclusion: The SCs were enriched from the testicular tissues of prepubertal New Zealand rabbits by a simple and effective protocol, which provides a basis for further theoretical researches and practical applications. J. Adv. Vet. Anim. Res., 8(2): 218-223, June 2021